Truth in Advertising and The Great Dollarization Scam - Thomas D. Willett (Claremont McKenna College, Department of Economics, 2001)
Various claims have been made by economist and others as to what caused the Asian crisis, as well as what caused its spread through much of East Asia. Here, we perform some initial testing of four hypotheses, including the dominant role of portfolio investors and hedge funds in initiating and spreading the crisis, moral hazard, and finally the role of Japanese banks in spreading trouble to countries in which they were the largest source of funds. All are found wanting as monocausal explanations, given the evidence we present. We believe that each likely has some weight in a more nuanced analysis, and it is now time to get past such simplistic approaches in order to produce a more complex, synthetic explanation of this episode. We expect that domestic investors moving their funds out of local currency will be an important part of that more complete explanation.
Keywords: 330